Evolution of the key alkaloid enzyme putrescine N-methyltransferase from spermidine synthase - Junker, Anne; Fischer, Juliane; Sichhart, Yvonne; Brandt, Wolfgang; Draeger, Birgit M. (Frontiers in Plant Science, 2013)
Putrescine N-methyltransferases (PMTs) are the first specific enzymes of the biosynthesis of nicotine and tropane alkaloids. PMTs transfer a methyl group onto the diamine putrescine from S-adenosyl-L-methionine (SAM) as coenzyme. PMT proteins have presumably evolved from spermidine synthases (SPDSs), which are ubiquitous enzymes of polyamine metabolism. SPDS use decarboxylated SAM as coenzyme to transfer an aminopropyl group onto putrescine. In an attempt to identify possible and necessary steps in the evolution of PMT from SPDS, homology based modeling of Datura stramonium SPDS1 and PMT was employed to gain deeper insight in the preferred binding positions and conformations of the substrate and the alternative coenzymes. Based on predictions of amino acids responsible for the change of enzyme specificities, sites of mutagenesis were derived. PMT activity was generated in Datura stramonium SPDS1 after few amino acid exchanges. Concordantly, Arabidopsis thaliana SPDS1 was mutated and yielded enzymes with both, PMT and SPDS activities. Kinetic parameters were measured for enzymatic characterization. The switch from aminopropyl to methyl transfer depends on conformational changes of the methionine part of the coenzyme in the binding cavity of the enzyme. The rapid generation of PMT activity in SPDS proteins and the wide-spread occurrence of putative products of N-methylputrescine suggest that PMT activity is present frequently in the plant kingdom.